Motion analyses of adolescent rugby union players: a comparison of training and game demands. - Hartwig, Timothy B; Naughton, Geraldine; Searl, John (Journal of Strength & Conditioning Research, 2011)
Hartwig, TB, Naughton, G, and Searl, J. Motion analyses of adolescent rugby union players: A comparison of training and game demands. J Strength Cond Res 25(4): 966-972, 2011-This research described the physiological demands of participation in adolescent rugby union including positional differences and the degree to which training practices replicate game demands. Between 2003 and 2008, 118 male adolescent rugby players aged 14 to 18 years were recruited from 10 teams representing 3 levels of adolescent rugby. Time-motion analyses using global positioning satellite tracking devices (SPI10; GPSports Systems Pty Ltd 2003) and computer-based tracking software (Trak Performance; Sports Tec Pty Ltd) applied to video footage determined player movement patterns 161 times during rugby training sessions and 53 times during rugby games. Compared with rugby training, rugby games were consistently characterized by more time spent jogging (14 vs. 8%), striding (3.2 vs. 1.3%), and sprinting (1.3 vs. 0.1%) (p < 0.001). Players also covered greater distances (4000 ± 500 vs. 2710 ± 770 m) and performed more sprints (21.8 vs. 1) during games compared with training (p < 0.001). The average sprint duration of 2 seconds was similar in games and training; however, the frequency of sprint efforts in training sessions was low (1 per hour). A major finding of this study is the disparity between physical game demands and on-field rugby training practices in adolescent players determined using time-motion analyses. Sprint pattern differences between games and training in particular could have important implications for player performance during competition. Results of this study should assist in the development of game-specific training sessions and drills that provide the kinds of physically demanding experiences observed in games. Additionally, coaches could assist in the management of adolescent players' participation loads by increasing the intensity and specificity and decreasing the volume of training.